Filsafat Ekonomi: Basis Pengembangan Kewirausahaan bercorak Etika Sosial - Pawenang, Supawi (Manajemen Bisnis Syariah, 2011)
This writing criticizes the philosophy of entrepreneurship occurring in Indonesia currently. For that reason, the discussion is philosophical in nature with the ethics as the subject of methodology. Considering the comprehensive study, the philosophical root is found that the entrepreneurship currently tends to be individualist ethics in nature. This condition is actually in contradiction with Bung Karno and Bung Hatta’s thought, when initiated the economic development system, emphasizing more on the basis of social ethics. There is a fundamental difference of this ethics basis. In individual ethics, the entrepreneur is more oriented to the maximum advantage with transactional character. Meanwhile, in the social ethics, the orientation is the business sustainability, by emphasizing on the deontological properties that is more reciprocal in nature.   Keywords: Individual Ethics, social ethics, entrepreneurship